Foraging strategy switch of a top marine predator according to seasonal resource differences - O'Toole, Malcolm D.; Lea, Mary-Anne; Guinet, Christophe; Schick, Robert; Hindell, Mark A. (Frontiers in Marine Science, 2015)
The spatio-temporal variability in marine resources influences the foraging behaviour and success of top marine predators. However, little is known about the links between these animals and ocean productivity, specifically, how plankton density influences their foraging behaviour. Southern elephant seals (Mirounga leonina) have two annual at-sea foraging trips: a two month post-breeding foraging trip (Nov – Jan) that coincides with elevated summer productivity; and an eight month post-moulting foraging trip (Feb – Oct) over winter, when productivity is low. Physical parameters are often used to describe seal habitat, whereas information about important biological parameters is lacking. We used electronic tags deployed on elephant seals during both trips to determine their movement and foraging behaviour. The tags also recorded light, which measured the bio-optical properties of the water column, the bulk of which is presumably influenced by phytoplankton. We investigated the relationship between plankton density and seal foraging behaviour; comparing trends between summer and winter trips. We found a positive relationship between plankton density and foraging behaviour, which did not vary seasonally. We propose that profitable concentrations of seal prey are more likely to coincide with planktonic aggregations, but we also acknowledge that trophic dynamics may shift in response to seasonal trends in productivity. Seal prey (mid-trophic level) and plankton (lower-trophic level) are expected to overlap in space and time during summer trips when peak phytoplankton blooms occur. In contrast, aggregated patches of lower trophic levels are likely to be more dispersed during winter trips when plankton density is considerably lower and heterogeneous. These results show that southern elephant seals are able to exploit prey resources in different ways throughout the year as demonstrated by the variation observed between seal foraging behaviour and trophic dynamics.